Teleculture: Kajian Pengaruh Dan Dampak Televisi Terhadap Manusia Modern - Ari Abi Aufa (Fakultas Syariah dan Adab Universitas Nahdlatul Ulama Sunan Giri, 2020)
In the midst of its massive use of smartphones by almost all modern people, television remains present in their daily lifes, filling their free time with various information and entertainment. Although television is no longer the only thing that dominates modern people, the role played by television remains large and even still influences the habits and culture of modern people. This research is a library research that aims to find the influence and impact caused by television on modern people by using the perspective of technology philosophy and human philosophy. Based on the research that has been done, television is proven to still have a very large impact on modern people, on their character, behavior and even on their existence, positively and negatively. The dominance of television in shaping the character of the younger generation still seems very large. This is evident in the lifestyle of modern society that is so easy to imitate the style of artists or public figures who often appear on television and get strong branding. This can have a positive or negative effect, depending on which side is followed from the behavior of a public figure. But the more important thing is the freedom for everyone to be himself, to be authentic, and not just follow the flow desired by a television program producer.